Influences of farming practices on soil properties and the 2-Acetyl-1-pyrroline content of Khao Dawk Mali 105 rice grains - Chinachanta, Kawiporn; Herrmann, Laetitia; Lesueur, Didier; Jongkaewwattana, Sakda; Santasup, Choochad; Shutsrirung, Arawan (Hindawi Limited, 2020)
Khao Dawk Mali 105 (KDML105) is a premium fragrant rice variety and is widely grown in )ung Kula Rong Hai (TKR), northeast )ailand. In the present study, the influence of organic and conventional rice farming (ORF and CRF, respectively) in TKR farmers’ paddy fields on soil properties and their relationship with 2-acetyl-1-pyrroline (2AP) in KDML105 rice grains were investigated. )e results indicated that the ORF system had a strong positive effect on major soil quality indicators and the 2AP content in the rice grains. )e soil organic matter (SOM) was approximately twice as much in the ORF than in the CRF system, thus leading to much higher total nitrogen (TN), humic acid (HA), and microbial populations in the ORF system.)ehigher SOM in the ORF system not only enhanced the soil quality indicators but also contributed to approximately 3.5 times higher 2AP than in the CRF system. Principle component analysis indicated a close correlation among SOM, TN, HA, and microbial population under the ORF system; these variables exhibited strong correlations with the 2AP contents in KDML105 rice grains.